2024
DOI: 10.3390/cancers16050896
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients with Sinonasal Cancers in a Population-Based Registry, Lombardy, Italy, 2008–2023

Dario Consonni,
Simona Stella,
Nerina Denaro
et al.

Abstract: Sinonasal cancers (SNCs) are rare malignancies associated with occupational exposures. The aim of this study was to analyse the survival of SNC patients using data from the population-based SNC registry of the Lombardy region (10 million people), Italy. We included epithelial SNC cases registered in 2008–2020 and followed-up for vital status until 31 July 2023. Multivariate flexible parametric models with time-dependent covariates were fitted to calculate excess hazard ratios (EHRs) and 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Moreover, male sex and older age at diagnosis were associated with reduced survival [ 10 ]. A recently published Italian study observed that age and cancer site had time-dependent effects on prognosis; especially within the first month after diagnosis, cancer morphology significantly influenced the prognosis, without differences between women and men [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, male sex and older age at diagnosis were associated with reduced survival [ 10 ]. A recently published Italian study observed that age and cancer site had time-dependent effects on prognosis; especially within the first month after diagnosis, cancer morphology significantly influenced the prognosis, without differences between women and men [ 11 ].…”
Section: Introductionmentioning
confidence: 99%